Orbital Volume Increases With Age: A Computed Tomography–Based Volumetric Study. Issue 6 (December 2019) - Ugradar, Shoaib; Lambros, Val
Abstract : Objective: The aim of the study was to determine whether the bony orbital volume (BOV) changes with age in males and females. Methods: This case-control study reviewed high-resolution (<1-mm slices) computed tomography (CT) scans of consecutive patients seen for 4 years. The scans were requested as part of the patient's routine care for symptoms related to sinus symptoms. Eligible participants were adults aged between 18 and 30 years and 60 and 75 years. Exclusion criteria included previous surgery, any medical conditions that might affect the bone or soft tissue of the orbit, and any abnormalities seen on imaging. Male patients aged between 18 and 30 years were compared with males aged 60 to 75 years. The same was done for females. The main outcome measure was measurement of the BOV. Both orbits of each patient were included using the generalized estimating equation, to avoid any bias from correlation between 2 orbits of the same patient. Results: A total of 240 orbits from 120 patients were used for this study. Each age group contained 30 patients. There were no significant differences in the ages between males and females in each age category ( P = 0.88 for ages 20–30 years and P = 0.74 for ages 60–75 years). The mean (SD) BOV for females aged between 20 and 30 years was 19, 153.69 mm 3 (3776.21), whereas that for females aged between 60 and 75 years was 20, 939.38 mm 3 (2837.34). The difference between the groups was significant (Pr(>|W|) = 0.05). The mean (SD) BOV for males aged between 20 and 30 years was 22, 2721 mm 3 (2977.35), whereas that for males aged between 60 and 75 years was 22, 892.92 mm 3 (2389.46) (Fig. 1). The difference between these 2 groups was not significant (Pr(>|W|) = 0.40). The mean BOV was significantly greater for males than females ( P ⩽ 0.01) across both age groups. Conclusions: This study found that female orbits expand with age, whereas male orbits showed no significant changes. Changes to the orbital volume in females may contribute to the appearance of aging.